The first report of a Campanian palaeo-wildfire in the West Antarctic Peninsula - Manfroi, Joseline (2014)
The analysis of palaeofloras and the related palaeoecological conditions is of great importance for the understanding of past environmental and palaeoclimatic events in Antarctica. At the end of the Cretaceous, subtropical forests developed there because of wet and temperate climate conditions. On the Antarctic Peninsula, which is geologically characterized by a forearc context, volcanic activity caused by tectonics favours the ignition of vegetation fires. In the present study, the occurrence of palaeo-wildfires during the Upper Cretaceous is demonstrated for the Rip Point outcrop on Nelson Island, South Shetland Islands. During Brazilian expeditions to the area, macroscopic charcoalwas collected and subsequently analysed under a stereomicroscope and scanning electron microscope (SEM). The charred wood remains were identified as belonging to conifers, which were important components of the Antarctic palaeoflora during the Cretaceous. A reviewof the data published thus far regarding palaeo-wildfires in the Southern Hemisphere confirms that the charcoal remains analysed here are the first to verify the occurrence of palaeo-wildfires in the upper Campanian levels of the West Antarctic Peninsula.